Marijuana Use, Alcohol Use, and Sexual Intercourse among Truant Adolescents. Issue 4 (October 2020) - Graves, Hannah R.; Hernandez, Lynn; Kahler, Christopher W.; Spirito, Anthony
Background: Adolescence is a time in development when many initiate problem behaviors, including alcohol use, marijuana use, and sexual intercourse. Although research has shown that these behaviors tend to co-occur, little is known about their daily co-occurrences, particularly among high-risk groups such as truant adolescents. This study investigated the influence of marijuana and alcohol use on the odds of engaging in sexual intercourse on a daily level among a sample of truant adolescents. Methods: Daily-level data from 76 at-risk, truant adolescents (46 male, 30 female) between the ages of 13 and 19 years who reported alcohol use, marijuana use, and sexual intercourse over a 90-day retrospective recall period were analyzed. Results: General estimating equations analyzing 6840 days and controlling for age, gender, and school days demonstrated that the use of marijuana and/or alcohol on a given day were associated with significantly increased odds of engaging in sexual intercourse on the same day. A significant interaction suggested that marijuana use on a given day increased the odds of engaging in sexual intercourse on that day among occasional marijuana users, yet not among frequent users. Additionally, a significant interaction suggested that frequent alcohol users had higher odds of engaging in sexual intercourse than those who used alcohol less frequently. Conclusions: This study suggests that experimenting with marijuana and alcohol increases truant adolescents' odds of also engaging in sexual intercourse. These results bridge the gap in the literature by investigating the daily-level associations and frequency of substance use and sexual intercourse among truant adolescents. This study demonstrates that among truant adolescents, substance use and sexual intercourse do not function independently; therefore, it is important to address the intersection between substance use and sexual behaviors during intervention development if sustained behavioral change is expected.